2012
DOI: 10.5688/ajpe7619
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Workshop About Aging on the Empathy Scores of Pharmacy and Medical Students

Abstract: Objective. To measure changes in pharmacy and medical students' empathy scores after a 40-minute workshop during which students observed and discussed a theatrical performance about the challenges of aging. Methods. First-year pharmacy and medical students (n 5 187 and n 5 183, respectively) participating in the workshop observed and discussed a 10-minute performance in which students enacted problems and concerns faced by elderly patients. The Jefferson Scale of Empathy (JSE) was administered just prior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 39 publications
9
72
2
5
Order By: Relevance
“…Whilst some authors have found that dental and other health professional students can be taught methods to increase empathy 2 others have found that increases may be short-lived 15,16 Still others have argued that empathy cannot be taught. 17 Even then empathy should be considered an important element in patient care and a significant factor of overall physician competence that must be enhanced during dental education, and applied in the practice of dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some authors have found that dental and other health professional students can be taught methods to increase empathy 2 others have found that increases may be short-lived 15,16 Still others have argued that empathy cannot be taught. 17 Even then empathy should be considered an important element in patient care and a significant factor of overall physician competence that must be enhanced during dental education, and applied in the practice of dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Students used a second unique identification code for their pre-and post-workshop collaboration instrument forms so their scores could be paired for more powerful statistical analysis of changes occurring in association with the interprofessional workshop. Students selected a second identification code because we found in prior studies 10 that students do not always recall their codes over several weeks or months.…”
Section: Methodsmentioning
confidence: 99%
“…4 By using regular assignments to elicit and perform critical reflection on difficult issues in the healthcare professions, professional education, and life, we have succeeded at modestly increasing cognitive empathy and patient-centered orientation scores in healthcare professions students. 3,5,10,11 The efforts also included a number of workshops 3,5,11 involving activities such as watching and discussing a performance about the challenges of aging. 10 While such interventions helped to improve students' empathy and patient-centered orientation scores, changes in their interprofessional collaboration scores had not been measured using a validated instrument.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the studies about empathy show that empathy declines during medical school (Hojat et al, 2004;Stepien & Baernstein 2006;Chen et al, 2007;Newton et al,2008;Fernandez Olano et al, 2008;Lim et al, 2011;Neumann et al, 2011;Van Winkle et al, 2012;Chen et al, 2012;Shariat & Habibi 2013). Unsuitable learning environments, cynicism/loss of idealism (Hojat et al, 2004;Newton et al, 2008), distress (Neumann et al, 2011), hidden curriculum (Eikeland et al, 2014), negative role-models, a high volume of materials to learn, time pressure, patient factors and overreliance on computer-based diagnostic and therapeutic technology can affect the students and cause a decline in empathy.…”
Section: Introductionmentioning
confidence: 99%